LOGISTICS CUSTOMER SATISFACTION IN INDONESIA A SYSTEMATIC LITERATURE REVIEW WITH FOCUS ON THE ROLE OF LOGISTICS SERVICE (Proceeding of SINERGY, 2026)
Over the past decade, Indonesia’s logistics industry has experienced very significant growth, driven by the rapid expansion of e-commerce, supply chain digitalization, and the increasing scope of national distribution needs. However, the rise in logistics sector revenues has not been accompanied by improvements in service quality, as reflected in the growing number of customer complaints. This condition indicates a structural gap between industry growth and service quality, making Logistics Customer Satisfaction (LCS) a strategic issue that requires comprehensive investigation. This study aims to identify and synthesize the dominant factors influencing LCS using a Systematic Literature Review (SLR) approach. The SLR process was conducted through four main stages: identification, screening, eligibility, and inclusion. From a total of 1,246 articles collected from five reputable international databases, 40 articles met the criteria for in-depth analysis. The synthesis results show that the factors influencing LCS can be classified into four main categories: Logistics Service Quality (52.50%), Last Mile Delivery (22.50%), Transportation Provider (17.50%), and Distribution (7.50%). These findings confirm that Logistics Service Quality is the most dominant factor shaping logistics customer satisfaction. This study contributes by developing an integrated, evidence-based conceptual map of LCS, which is expected to serve as a strategic foundation for logistics service providers and policymakers in improving service quality and customer orientation in Indonesia.